The 5' end of poliovirus mRNA is not capped with m7G(5')ppp(5')Np. - Nomoto, A (1976)
Poliovirus was grown in HeLa cells in the presence of phosphorus-32 and actinomycin D. Three to four hours after infection, viral mRNA was recovered from polyribosomes and its identity verified by two-dimensional gel electrophoresis of RNase T1 digests. Digestion of the viral [32P]mRNA with RNase T2 and separation of the products by ion exchange chromatography at pH 5 yielded pUp as possible 5' terminus but no "capping group" of the structure m7G(5')ppp(5')Np. Total cytoplasmic [32P]RNA of HeLa cells, on the other hand, was found to contain capping groups. Neither the capping group nor ppNp or pppNp was found in an RNase T2 digest of poliovirion [32P]RNA, in agreement with previous results [Wimmer, E. (1972) J. Mol. Biol. 68, 537-540]. The data indicate that 5'-terminal m7G(5')ppp(5')Np is absent from poliovirus RNAs and, therefore, is not involved in poliovirus protein synthesis.